PERBEDAAN KEMAMPUAN INTERAKSI SOSIAL REMAJA KORBAN BULLYING DITINJAU DARI JENIS KELAMIN - Yoanda Novenaida, Suci; Meivilona Yendi, Frischa; Taufik, Taufik; Sukmawati, Indah (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This research is motivated by the fact that there are still teenage victims of bullying who do not interact well with their environment. Gender is one of the factors that influence social interaction. This research aims to examine whether there are significant differences in social interactions between male adolescent victims of bullying and female adolescent victims of bullying. This study used a comparative descriptive approach, with a sample of 103 adolescent victims of bullying at SMPN Kota Padang. The results showed that there was a difference in the ability of social interaction between male adolescent victims of bullying in the high category (57.63%) and the ability of social interaction between female adolescent victims of bullying in the medium category (72.73%) and there was a significant difference in the ability of social interaction between male adolescent victims of bullying and female adolescent victims of bullying with a significance level of 0,000.